1992
DOI: 10.1073/pnas.89.19.9191
|View full text |Cite
|
Sign up to set email alerts
|

Phagocytosis of liposomes by human platelets.

Abstract: We have shown that platelets are capable of phagocytosing liposomes rather than simply sequestering par- membrane marker. Uptake was inhibited by the addition of EDTA, cytochalasin B, or 2,4-dinitrophenol and iodoacetate to the medium. Results from the serotonin release assay, microaggregation assay, fluorescein diacetate membrane integrity assay, and electron microscopy indicate that neither the conditions for loading nor phagocytosis ofliposomes significantly alter platelet function or morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…Platelets have been reported to internalize nanoparticles through the open canalicular system (OCS), a surface-connected system of channels within the core of the platelet, and by cell engulfment and trafficking to storage vacuoles. [18] This is consistent with the results observed here, including the inability of any single inhibitor to completely abrogate uptake.…”
Section: Resultssupporting
confidence: 91%
“…Platelets have been reported to internalize nanoparticles through the open canalicular system (OCS), a surface-connected system of channels within the core of the platelet, and by cell engulfment and trafficking to storage vacuoles. [18] This is consistent with the results observed here, including the inability of any single inhibitor to completely abrogate uptake.…”
Section: Resultssupporting
confidence: 91%
“…Many studies have shown that platelets appear to internalize particles but that these particles are located in the open canalicular system (OCS), as opposed to undergoing internalization into a phagosome (26,28,38,43). These studies differ in their target choices, preparation techniques, and staining methods.…”
Section: Discussionmentioning
confidence: 99%
“…For example, human platelets have been observed to phagocytose liposomes, erythrocyte fragments, some bacteria, viruses, and even latex beads (26,28,36,43). Although the mechanism(s) for phagocytosis and the fate of internalized particles are disputed, nonetheless, platelets can sequester various targets (38,39).…”
mentioning
confidence: 99%
“…This mechanism alone would require that little membrane trafficking occur in the platelet because rapid membrane turnover would lead to membrane mixing and uniformity of SNARE protein distribution. However, constitutive endocytosis 1,3,55 and true phagocytosis 56,57 have been reported in platelets. In most cells, endocytosis is accompanied by exocytosis to maintain a relatively constant plasma membrane surface area.…”
Section: Discussionmentioning
confidence: 99%